Peptide nucleic acid-immobilised paper combined with multiplex recombinase polymerase amplification for the ultrasensitive and rapid detection of rifampicin-resistant tuberculosis - Nuttapon Jirakittiwut; Panuwat Sathianpitayakul; Pitak Santanirand; Yukihiro Akeda; Tirayut Vilaivan; Panan Ratthawongjirakul (Scientific Reports)
Abstract Rifampicin-resistant tuberculosis (RR-TB) is a critical issue with significant implications for patient care, public health, and TB control efforts that necessitate comprehensive strategies for detection. This study presents a novel point-of-care diagnostic tool for RR-TB detection employing a peptide nucleic acid (PNA)-paper-based sensor combined with isothermal recombinase polymerase amplification (RPA). The sensor targets mutations in codons 516, 526, and 531 of the rpoB gene, the top three common mutations associated with rifampicin-resistant strains. PNA probes specifically recognised wild-type sequences, generating a visual signal through a reverse hybridisation assay. The absence of a signal was observed when the mutant strains were detected because of the inability to bind the mutant sequence. Our proof-of-concept assay displayed high accuracy (100% for detecting mutations at codons 516, 526, and 531), a short turnaround time (110 min), no cross-reactivity with other bacterial pathogens, and ultrasensitivity. This PNA-paper-based sensor model can be a valuable diagnostic tool for RR-TB detection, providing an accessible diagnostic platform that can be advantageous in resource-limited settings where sophisticated laboratory infrastructure may be lacking.